Comparative Study of the Effect of Structural Parameters on the Flexibility of Endovascular Stent Grafts - Ying Guan; Jing Lin; Zhihui Dong; Lu Wang (Advances in Materials Science and Engineering)
The complication of stent graft-induced new entry (SINE) after thoracic endovascular aortic repair (TEVAR) may be caused by the spring-back force of both ends of the stent grafts. Spring-back force, which is exerted by the curvature and ends of stent grafts on the greater wall of the aorta, suggests poor flexibility. Research on stent graft flexibility via design optimization has been widely disregarded. Thus, this study investigates the relationship between stent graft structure and flexibility by measuring bending and spring-back forces. Stent spacing (5, 10, and 15 mm), apex angle (30° and 45°), and strut configuration (Z- and M-stented) were considered for the structural parameters. The overall tendency of spring-back and bending forces was similar. The stent graft with 15 mm spacing attained the lowest force level. The force difference between samples with 30° and 45° apex angles became prominent as the curving angle increased. The sample with 45° stent apex attained low force value. The Z-stented graft obtained a lower force than the M-stented graft with the same number of struts per hoop. Consequently, optimal flexibility was obtained when the structural design was characterized by long stent spacing, big stent apex angle, and Z-type strut configuration.